PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PICTURE AND PICTURE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA N 1 UKUI TAHUN AJARAN 2009/2010 - Mariani Natalina; Yustini Yusuf; Desy Rahmayani (Program Studi Pendidikan Biologi, 2011)
This Research aim to increase result and activity learn student by using model study of co-operative of picture and picture at class of XI Science SMA N 1 Ukui school year 2009-2010. This research represent research of class action, done in May 2010. Research Subject is class student of XI Science SMAN 1 Ukui amounting to 21 people, consist of 10 men and 11 women. With research parameter : student activity, result of learning and teacher activity. Activity student mean at first cycle that is 78,41% (good) and 82,28% (good) at Second cycle. Mean Absorpsion student at first cycle , first meeting owning mean 78,33 ( good),second meeting that is 73,16 (enough),third meeting that is 76,19 (good), and daily restating mean 72,47 (enough). At second cycle,first meeting owning mean 76,5 (good),second meeting that is 81,5 (good) and daily restating mean that is 78,1 (good). Complete learn student at second cycle is 85,7% (very good) and 95 % (very good) at second cycle. Appreciation of group first cycle there is 1 group of with super predicate. and 3 group of predicate, while at second cycle all group have excitement predicate. The rate actitivity is 96,96% (very good) and 100% (very good) at second cycle. From result of research can be concluded that usage of model study of co-operative of picture and picture can improve result and activity learn class student biology of XI Science SMA N Ukui in the year.